2020
DOI: 10.1073/pnas.2014294117
|View full text |Cite
|
Sign up to set email alerts
|

Coexpressed subunits of dual genetic origin define a conserved supercomplex mediating essential protein import into chloroplasts

Abstract: In photosynthetic eukaryotes, thousands of proteins are translated in the cytosol and imported into the chloroplast through the concerted action of two translocons—termed TOC and TIC—located in the outer and inner membranes of the chloroplast envelope, respectively. The degree to which the molecular composition of the TOC and TIC complexes is conserved over phylogenetic distances has remained controversial. Here, we combine transcriptomic, biochemical, and genetic tools in the green alga Chlamydomonas (Chlamyd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 85 publications
0
51
0
Order By: Relevance
“…Among the difficulties raised concerning the proposed role of the 1-MDa complex in protein import, one is of a phylogenetic nature: the absence of several of the complex’s main components from the grass family of monocots ( de Vries et al, 2015 ; Bolter and Soll, 2016 ). In contrast, recent evidence strongly supports the function of the complex in a chlorophyte alga ( Ramundo et al, 2020) . It has been argued that an alternative form of the TIC20 translocon may operate in grasses and that this utilizes orthologs of TIC20-IV which is expressed and presumably active in roots of Arabidopsis ( Kasmati et al, 2011 ; Nakai, 2015a ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the difficulties raised concerning the proposed role of the 1-MDa complex in protein import, one is of a phylogenetic nature: the absence of several of the complex’s main components from the grass family of monocots ( de Vries et al, 2015 ; Bolter and Soll, 2016 ). In contrast, recent evidence strongly supports the function of the complex in a chlorophyte alga ( Ramundo et al, 2020) . It has been argued that an alternative form of the TIC20 translocon may operate in grasses and that this utilizes orthologs of TIC20-IV which is expressed and presumably active in roots of Arabidopsis ( Kasmati et al, 2011 ; Nakai, 2015a ).…”
Section: Discussionmentioning
confidence: 99%
“…Tic20, Tic110, and Tic40 are considered components of the TIC import machinery in the chloroplast; however, Kikuchi et al (2013) reported that only Tic56, Tic100, and Tic214 were isolated from the 1-megadalton complex when using a tagged form of Tic20. Ramundo et al (2020) also demonstrated that the TIC complex contains Tic20, Tic56, Tic100, and Tic214 by combining transcriptomic, biochemical, and genetic tools in the green alga Chlamydomonas, indicating that the complex is widely conserved among photosynthetic organisms ( Ramundo et al, 2020 ). This result conflicts with our finding of the GmTic110a interaction with GmTic20 in the above studies, even though a similar interaction was also reported previously ( Kouranov et al, 1998 ; Chen et al, 2002 ; Inaba et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have significantly revised the long-accepted “classical” model for chloroplast protein import: In the classical model, Tic110 ( Ishida and Terakura, 1987 ; Inaba et al, 2005 ), Tic40 ( Stahl et al, 1999 ; Chou et al, 2003 ), Tic20 ( Kouranov and Schnell, 1997 ; Kasmati et al, 2011 ), and Tic21 ( Vitale et al, 2015 ) are the main components, but they are not found in the translocon proposed by Nakai (2015 , 2018 , 2020) . In the revised model, the 1-megadalton TIC complex consists of Tic214 (ycf1; de Vries et al, 2007 ; Bölter and Soll, 2017 ), Tic100 ( Oshima et al, 1987 ; Ramundo et al, 2020 ), Tic56 ( Köhler et al, 2015 , 2016 ), Tic20 ( Kikuchi et al, 2009 ), and Tic21 ( Kouranov and Schnell, 1997 ; Teng et al, 2006 ), which functionally and physically cooperate with the ATP-driven import motor YCF2/FTSHI complex ( Kikuchi et al, 2013 , 2018 ; Thomson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the common ancestral origin of cyanobacteria and C 3 plant chloroplasts is partly identified in shared phylogeny of many of their outer membrane proteins ( Day and Theg, 2018 ), and this might suggest potential for successful transfer of cyanobacterial membrane components to the chloroplast IEM. However, the transfer of genes from the plastome to the nucleus during C 3 plant evolution means both the inversion of directional insertion of membrane proteins ( Day and Theg, 2018 ), and the emergence of cTPs to enable protein trafficking through the TIC-TOC complex and to the correct membrane ( Figure 3 ; Knopp et al, 2020 ; Ramundo et al, 2020 ).…”
Section: How Can We Get C I Uptake Systems Into the Chloroplast?mentioning
confidence: 99%